1996 Olympic Games in Atlanta: The best female volleyball-teams: Cuba - Fröhner, B. (The Coach, 1996)
Cuba`s initial line-up has remained almost stable since 1992. In this advantageous constant formation the style of playing has not been changed in general, neither by the substitutions (setter: O´Farill for Izquierdo, middle blocker/quick attacker: partially Fernandez for Carvajal). The Cuban team is the only one playing with two setters who are very skilled in attacks. This concept enables the team to dominate the international top. But in Atlanta it was not as superior as in the past and had to accept two losses on the road to the Olympic title (against Brazil and Russia in the preliminaries). But its great competition experience made it possible to recover and to enhance the performance just in the moment it was needed to win the Olympic title again. Once again the physical superiority made its way (height and spiking power in the attacks, co-ordinated,compact and offensive block) without applying back row attacks and jumping spike services as elements of modern offensive volleyball. In the serve reception Cuba plays with a four-players-formation with two main receivers. The back row players have a very far behind position and cover the majority of the reception actions. Short services are received by the front players (by preference by a setter). The serve reception is very reliable and is performed to approximately 70% by the effective frontal technique. There is no need for a maximum precision in the initial phase of the attack arrangement since the accuracy of performance is always good enough to prepare the preferred high attacks and second attacks without any trouble.